Language Teachers' Perceptions and Use of Extended Reality. (10th February 2023) - Kaplan-Rakowski, Regina; Papin, Kevin; Hartwick, Peggy
Abstract : Extended reality (XR) is rapidly gaining attention and popularity; however, scholars confuse what XR technologies are and how they can be applied in language education. This qualitative, exploratory study unveils language teachers' perceptions of XR, which is an umbrella term for virtual reality (VR), augmented reality (AR), and mixed reality (MR). Understanding teachers' perceptions regarding XR is a necessary step toward successful integration, adaptation, and diffusion of these technologies. Based on 110 survey respondents and 10 focus group interviewees, we report on how language teachers apply XR and what potential benefits and barriers they face. This study contributes to the mutual understanding of XR in the computer-assisted language learning community, and it provides examples of practical applications of XR to facilitate language learning and teaching.